EARLY PERMIAN TARIM LARGE IGNEOUS PROVINCE IN NORTHWEST CHINA : tectonics, petrology ... geochemistry, and geophysics. - Yang, Shufeng; Chen, Hanlin; Li, Zilong; Li, Yinqi; Yu, Xing (Advances in China's basic research., 2018)
The Early Permian Tarim Large Igneous Province in Northwest China: Tectonics, Petrology, Geochemistry, and Geophysics is the first book to introduce the Early Permian Tarim Large Igneous Province. Based on more than twenty years of study, this book systematically presents time-spatial, geochemical and geodynamic features, along with the metallogenesis and magma evolution of the Early Permian Tarim Large Igneous Province. Furthermore, it provides a new geodynamic model for Large Igneous Provinces. It is intended for researchers and graduate students in tectonics, igneous petrology, geochemistry, geophysics, earth evolution and planetary geology in addition to mining industry professionals.